2017
DOI: 10.1136/bmjopen-2017-016940
|View full text |Cite
|
Sign up to set email alerts
|

The HAT TRICK programme for improving physical activity, healthy eating and connectedness among overweight, inactive men: study protocol of a pragmatic feasibility trial

Abstract: IntroductionPhysical activity, healthy eating and maintaining a healthy weight are associated with reduced risk of cardiovascular disease, type 2 diabetes and cancer and with improved mental health. Despite these benefits, many men do not meet recommended physical activity guidelines and have poor eating behaviours. Many health promotion programmes hold little appeal to men and consequently fail to influence men’s health practices. HAT TRICK was designed as a 12-week face-to-face, gender-sensitised interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 73 publications
0
30
0
Order By: Relevance
“…This body of research, and research conducted in Australia [50,[73][74][75][76][77][78][79][80] and Canada (e.g., [36,69,70,72], demonstrates that, with attention to cultural constructions of masculinity in relation to health and health behavior, public health interventions can be gender-sensitized so that they both appeal to men and support them in sustainable lifestyle changes, which may cascade to other family members and to wider society. The successful scale-up and scale-out of FFIT, as documented here, profoundly contest the view that men 'won't' take part in such programs and present an ongoing challenge for the public health community to find the right 'hooks' to engage men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This body of research, and research conducted in Australia [50,[73][74][75][76][77][78][79][80] and Canada (e.g., [36,69,70,72], demonstrates that, with attention to cultural constructions of masculinity in relation to health and health behavior, public health interventions can be gender-sensitized so that they both appeal to men and support them in sustainable lifestyle changes, which may cascade to other family members and to wider society. The successful scale-up and scale-out of FFIT, as documented here, profoundly contest the view that men 'won't' take part in such programs and present an ongoing challenge for the public health community to find the right 'hooks' to engage men.…”
Section: Discussionmentioning
confidence: 99%
“…Its name reflects the program's tripartite goals (to increase physical activity, encourage healthy eating and strengthen social connections amongst men) and the design of the program materials "aligns with participant identities as ice hockey fans and men" [71] (p. 2159). The pilot feasibility trial of HAT TRICK is reported elsewhere [72].…”
Section: Scale-outmentioning
confidence: 99%
“…It would be expected that hypertension was predicted by unhealthy exercise as aerobic exercise has significant favorable impacts on blood pressure ( Wen & Wang, 2017 ). While exercise has been espoused as a health promotion practice that appeals to many men, a recent review by Bottorff, Oliffe, et al (2015) revealed few programs that were explicitly designed for men, and/or formally evaluated ( Bottorff, Seaton, et al, 2015 ; Caperchione et al, 2017 ). Numerous research teams ( Faraut et al, 2012 ; Palagini et al, 2013 ; Wang et al, 2015 ) have examined the effect of sleep on hypertension, and while there are conflicting reports, many large studies have highlighted that reduced sleep having a significant impact on hypertension, most of which are unrelated to other conditions such as obstructive sleep apnea ( Calhoun & Harding, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, there were suggested increases in physical activity that appeared to be sustained for a short time after the intervention ceased, and in the likelihood of public transit use. Given the challenges of engaging older men in physical activity and their health (Caperchione et al, 2017), and the substantial benefits of physical activity to health should we succeed in doing so, we are encouraged by these findings.…”
Section: Discussionmentioning
confidence: 99%